Perbudakan ISIS terhadap Perempuan Etnis Yazidi di Irak sebagai Kejahatan terhadap Kemanusiaan dalam Konflik Bersenjata - Ardiyanti, Oriza; Utomo, Tri Cahyo (Journal of International Relations, 2019)
When ISIS seized control of the Iraqi territory in August 2014, the extremist group had carried out various forms of crimes against humanity towards multiple ethnic groups to launch their aim of forming a Islamic State. They have commited murder, torture, ill-treatment, religious coercion, imprisonment, and kidnappings accompanied by acts of sexual slavery, forced rape and pregnancy as happened in the Yezidi ethnic case in Iraq. ISIS has captured, sold, and raped them as slaves and caused victims to receive various types of physical and mental abuse. The aim of this study is to provide an overview of the reasons underlying ISIS for sexual slavery against Yezidi women in Iraq by using the concept of Crimes against Humanity to explain the facts in case studies. The results of this study indicate that ISIS background made Yezidi women in Iraq as prisoners of slaves due to their own justification of the Qur'an interpretation which discredited and subordinated women, so that women were freely sold and treated arbitrarily. In addition, ISIS's actions were driven by very promising business motives of the "slave market" and have contributed a huge income to the activities and the continuity of ISIS.